Exploring the climate-environment-health nexus: Insights for informed action - Harvey V. Fineberg (Field Actions Science Reports)
Human health, the environment, and climate change are intricately linked. The environment, encompassing physical, biological, and social dimensions, profoundly influences our health. Climate change, as a pervasive force, impacts human health directly, for instance through extreme weather events, and indirectly through phenomena like air pollution from wildfires, and alterations to ecosystem services. Our understanding of health has evolved over time from ancient philosophical roots to modern scientific insights. While the environment was gradually integrated into this understanding, climate change remains a pressing concern that is often overlooked in health policies. Addressing climate-related health risks demands a multi-faceted approach, drawing also on practices from Eastern and indigenous cultures that emphasize the interconnectedness of humans and the environment. Collective action and policymaking are essential to mitigate these risks, alongside individual contributions. Effective action entails adopting a preventive mindset and ambitious policies to reduce climate change drivers, mitigate impacts, and promote resilience in human populations. Overcoming the growing distrust of science through education and awareness is also crucial. As societies confront these challenges, it is imperative to envision a future where we not only survive but thrive as a society, embracing sustainability and resilience as guiding principles for a healthier and more equitable world.